The Jahn Teller and surface interactions in C60 nano systems - Alqannas, Haifa Saleh (2014)
Scanning Tunnelling Microscopy (STM) is the fastest possible method of imaging the molecular orbitals of the C[subscript]60 anions with resolution at the single atom level. For the particular anions of fullerene C[subscript]60, the splitting of the molecular orbitals due to the internal Jahn-Teller effects (JT) add further difficulties in understanding the published experimental images. In the current work, the effect of JT interaction on STM recorded images is studied. For higher charged states, the Coulomb interaction affects the distribution of electrons around the ion, and then as a consequence, the STM current. The external interaction between the molecule and the surface substrate is equally important. Symmetry analysis using group theory and Hückel molecular orbital (HMO) theory are applied in order to describe the influence of the surface interactions on JT minima associated with D[subscript]3d, D[subscript]5d, D[subscript]2h, and C[subscript]2h symmetries. It represents some fullerene anions, which are adsorbed to the surface with different orientations, such as pentagon, hexagon, and double-bond prone toward the surface. Several ions with higher charges are investigated, such as C2−60, C3−60, and C4−60. In case of high symmetry orientations, the JT minima of the ions on a surface are split into subgroups with equal energies, depending on the type of orientation. The interpretation of the experimental observations is always possible for any orientation from the JT minima distribution and the contribution to the images from different components of the degenerate molecular orbitals.